Méthodes d'appréciation de la qualité physico-chimique et microbiologique des laits réceptionnés au niveau d'une unité de transformation - Mohammed Cherif, Warda (My University, 2020)
The milk for human consumption is the full product of the total and uninterrupted milking of a female dairy healthy, well fed and not overworked. Contaminated, it may be a vector of transmission of pathogens to humans and may pose a risk to human health. Assessing the physico-chemical and microbiological quality of raw milk for consumption or processing is essential for consumer protection. It is both food and drink of great nutritional value, and is the traditional food of choice, providing for both humans and mammals a basic aliment almost complete. Microorganisms are also found in milk, which is considered as an ideal substrate for their development. The presence of many growth factors within this aliment will satisfy many of demanding microbial species, which are so difficult to grow in a less complete media. This study focuses on the evaluation of the microbiological quality of raw milk, results of a bacteriological analysis of 155 samples of bulk milk are:- A FAMT> 105 CFU/ml was found in 81.2% of our samples; - Fecal coli form bacteria are present within 18.06% of our samples; - Staphylococcus aureus and fecal Streptococci are present in 81.93 and 80.64% respectively.
Keywords: Milk; microbiological quality; physico-chemical quality